2024
DOI: 10.1200/jco.23.02005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Trastuzumab Deruxtecan in Patients With HER2-Expressing Solid Tumors: Primary Results From the DESTINY-PanTumor02 Phase II Trial

Funda Meric-Bernstam,
Vicky Makker,
Ana Oaknin
et al.

Abstract: PURPOSE Trastuzumab deruxtecan (T-DXd) is a human epidermal growth factor 2 (HER2)-directed antibody-drug conjugate approved in HER2-expressing breast and gastric cancers and HER2-mutant non-small cell lung cancer. Treatments are limited for other HER2-expressing solid tumors. PATIENTS AND METHODS This open-label phase II study evaluated T-DXd (5.4 mg/kg Q3W) for HER2-expressing (immunohistochemistry [IHC] 3+/2+ by local or central testing) locally advanced or metastatic disease after ≥1 systemic treatment, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(58 citation statements)
references
References 28 publications
2
55
0
1
Order By: Relevance
“…This is a human epidermal growth factor 2 (HER2)-directed ADC with a potent topoisomerase I inhibitor payload. The single-arm, multi-cohort phase II DESTINY-PanTumor02 basket trial evaluated trastuzumab deruxtecan (5.4 mg/kg once every 3 weeks) for HER2-expressing (immunohistochemistry [IHC] 3+/2+ as per ASCO/CAP gastric cancer scoring) advanced cancers after at least 1 line of systemic treatment or without standard options [ 31 ]. Within the cohort of 40 aCC subjects, 5 patients with IHC 1+ status were included after a protocol-specified interim analysis.…”
Section: Accmentioning
confidence: 99%
“…This is a human epidermal growth factor 2 (HER2)-directed ADC with a potent topoisomerase I inhibitor payload. The single-arm, multi-cohort phase II DESTINY-PanTumor02 basket trial evaluated trastuzumab deruxtecan (5.4 mg/kg once every 3 weeks) for HER2-expressing (immunohistochemistry [IHC] 3+/2+ as per ASCO/CAP gastric cancer scoring) advanced cancers after at least 1 line of systemic treatment or without standard options [ 31 ]. Within the cohort of 40 aCC subjects, 5 patients with IHC 1+ status were included after a protocol-specified interim analysis.…”
Section: Accmentioning
confidence: 99%
“…Furthermore, the ongoing phase 2 trial DESTINY-PanTumor-02, with results expected in April 2027, shows that T-DXd has broad activity across many tumor types with positive HER2 status, including ovarian cancers. Initial findings presented during the 2023 American Society of Clinical Oncology Annual Meeting revealed that among enrolled patients with ovarian cancers, there was an overall response rate of 45% and a complete response rate of 10% 32 . Evaluating HER2 status including those classified as HER2 “low” in EOC introduces new options for experimentation with potential therapy to improve the overall survival of such patients.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 120 patients with gynaecologic malignancies were included, in which objective response rate (ORR) among patients with cervical cancer was 50.0%. The ORR was particularly high in the HER2+ and HER3+ groups, suggesting that this treatment can be an option for HER2-positive GAS cases ( 54 ). This may offer a new treatment paradigm for this small subset of patients with GAS and should be explored further in prospective studies including antibody–drug conjugates as in non-small cell lung cancer or breast cancer.…”
Section: Clinical Pathological Featuresmentioning
confidence: 99%